When green meets green - Hans Degryse; Roman Goncharenko; Carola Theunisz; Tamas Vadasz (National Bank of Belgium, 2020)
What is the impact of environmental consciousness (i.e., being green) as borrower and as lender on loan rates? We investigate this question employing an international sample of syndicated loans over the period 2011-2019. We find that green firms borrow at a signifi- cantly lower spread, especially when the lender consortium can also be classified as green, i.e., when "green-meets-green". Further tests reveal that the impact of "green-meets-green" became significant and large negative only after the acceptance of the Paris Agreement in December 2015. We argue that this is evidence for lenders responding to policy events which affect environmental attitudes.
Keywords: A13; G21; Q51; Q58; 330; Paris Agreement; Green Firms; Green Banks; Bank Lending